Drug‐Drug Interaction of Letermovir and Atorvastatin in Healthy Participants. Issue 4 (14th February 2022) - McCrea, Jacqueline B.; Menzel, Karsten; Adedoyin, Adedayo; Cho, Carolyn R.; Fox‐Bosetti, Sabrina; Macha, Sreeraj; Zhao, Tian; Liu, Fang; Panebianco, Deborah; Stoch, S. Aubrey; Iwamoto, Marian
Abstract: Letermovir (MK‐8228/AIC246) is a cytomegalovirus (CMV) DNA terminase complex inhibitor for CMV prophylaxis in adult patients undergoing hematopoietic stem cell transplant. It is cytochrome P450 (CYP) 3A inhibitor and inhibits organic anion transporting polypeptide 1B1/3 and breast cancer resistance protein transporters. Atorvastatin (ATV), a commonly used treatment for hypercholesterolemia, is a substrate of organic anion transporting polypeptide 1B1, potentially breast cancer resistance protein, and CYP3A. As letermovir may be coadministered with ATV, the effect of multiple‐dose letermovir 480 mg once daily on the pharmacokinetics of single‐dose ATV 20 mg and its metabolites (ortho‐hydroxyatorvastatin [o‐OH‐ATV] and para‐hydroxyatorvastatin [p‐OH‐ATV]) was evaluated in an open‐label trial in healthy female adults (N = 14). ATV area under the plasma concentration–time curve from time 0 to infinity and maximum plasma concentration (Cmax ) increased ≈3‐fold with letermovir coadministration. The time to ATV Cmax also increased, while apparent clearance decreased. The exposures of o‐OH‐ATV and p‐OH‐ATV were comparable in the presence versus absence of letermovir; however, o‐OH‐ATV Cmax decreased by 60% with coadministration, while p‐OH‐ATV Cmax was similar. Due to the increase in ATV exposure with letermovir coadministration, statin‐associated adverse events such as myopathy should be closely monitored following coadministration. The dose of ATV should not exceed 20 mg daily when coadministered with letermovir.